Applicability of Euphorbia milii var splendens latex in the control of Biomphalaria tenagophila (Research, Society and Development, 2021)
The present work aimed to evaluate in vitro the molluscicidal activity and latex toxicity of Euphorbia milii var. splendens (Bojer ex Hook) Ursch & Leandri for the control of mollusks of the species Biomphalaria tenagophila. Specimens of E. milii var. splendens cultivated in the rural region of Pindamonhangaba were selected, from which latex was obtained by the transverse incision of the aerial parts. For the molluscicide test, adult mollusks of the species B. tenagophila were separated into groups of 10 and submitted to latex immersion at concentrations of 2.5 ppm, 1.25 ppm, 0.625 ppm, and 0.3125 ppm for 24 hours. In parallel, the toxicity of latex at a concentration of 0.3125 ppm was determined by testing with Artemia salina (mortality assessment) and using the Allium cepa test (determination of growth inhibition, amount, and weight of roots). It was observed an important molluscicidal activity of E. milii var. splendens latex at the various concentrations evaluated. In addition, it was also possible to observe moderate toxicity against A. salina nauplii and in the toxicity test with A. cepa. This demonstrates the potential of using latex from E. milii var. splendens to control populations of B. tenagophila species, not only for the observed molluscicidal activity but also for the moderate mortality of A. salina nauplii, whereas in the A. cepa test no change was observed in the parameters evaluated in relation to the control group, demonstrating safety for use in the environment.